RHEUMATOID ARTHRITIS-PRESENTATION AND OUTCOME OF MANAGEMENT - Muhammad Kaleem Shaukat; Noor Akbar Sial (Journal of University Medical & Dental College)
ABSTRACT Objectives: To study the presentation and outcome of management of rheumatoid arthritis at Madina Teaching Hospital and Independent Medical College Hospital, Faisalabad. Patients and Methods: A prospective study was done. One hundred and forty four patients of rheumatoid arthritis attending the Out Patient Department of Orthopedic Surgery in Madina Teaching Hospital Faisalabad, from January 2008 to June 2009, were analyzed. Every patient was treated with DMARDs along with NSAIDs and short course of Steroids. All the patients were followed for one year with monthly visits. No patient developed any new complication during treatment. Results: In 124 patients with Rheumatoid Arthritis there were 102 female and 22 male patients. The patient ages ranged from 15 to 70 years with mean age 28 years. Female to male ratio was almost 5:1. Most common presenting symptom was polyarthralgia with involvement of hand joints. Rheumatoid Factor was positive in 76% patients. Conclusion: Rheumatoid Arthritis is one of the common diseases, seen in the Out Patient Department of Orthopedic Surgery. Treatment with DMARDs can halt progression of the disease and help against the development of complications.